Dinamika Partai Keadilan Sejahtera di Denpasar Tahun 1998 -2014 - Cs, Nurjaya; Bagus Wirawan, Anak Agung; Inten Asmariati, Anak Agung (Humanis, 2017)
The changing of movement of Prosperous Justice Party was done considering important factors that come from Indonesia democracy context. Among them is to soften the ideology line in order of short-term interest of raising vote. The trick is to open the party gate for non-Muslims circle and positioned itself firmly on demanded or required issues by the public. Anti-corruption issues and consistency to escort good goverment will able to provide bigger benefit than maintaining the old base ideology and only expect from ideological voters. Nevertheless, the regeneration pattern still runstictly. Implications or contributions from Prosperous Justice Party presence in Denpasar in the period of 17 years had seemed better in comparison with another Islamic party in Denpasar. In accordance with the development platform that had been designed, Prosperous Justice Party in Denpasar has attempted to build Denpasar based on three field, which are the political field, the economy field, and social cultural field. These three field has one entity in realizing the Prosperous Justice Party vision for civilized, fair, and dignified Indonesia.
Keywords: Dynamics, Dakwah movement, Politic strategy